An association among poverty, economic growth, income inequality and unemployment in sri lanka: econometrics analysis - Suveeda, K.; Vijayakumar, S. (M-infiniti, 2015)
It is the fact that there is significant impact of unemployment, income inequality and economic growth on poverty incidence in Sri Lanka. The 78% of variation in poverty has been explained by unemployment, income inequality and economic growth. Accordingly, income inequality and unemployment have positive association with poverty while economic growth has negative relationship with poverty. The regression result clearly revels that even though economic growth is a significant variable; its impact on poverty is very margin in Sri Lanka.
Keywords: Poverty; Economic growth; Income inequality; Association; Marginal